Combined conceptual and supercritical numerical model of the Reykjanes peninsula - Sam Alexander Barton 1987- (2019)
Conceptual and numerical modelling of geothermal systems has become an invaluable tool in the successful exploration, utilisation and long term management of geothermal resources. These tools provide valuable input into informed decisions to sustainably utilise these resources. With increased interest and subsequent exploration of the roots of high-temperature geothermal systems, modelling technology and techniques are rapidly evolving to accurately represent the conditions found at these great depths. One such geothermal system is the Reykjanes peninsula which is located in South-West Iceland and is the landward extension of the divergent plate boundary of the mid-Atlantic ridge. It is home to three geothermal systems namely Reykjanes, Eldvörp and Svartsengi, two of which are being utilised for electricity and heat production. This study investigates a workflow used to develop a new combined regional conceptual and supercritical numerical model of the Reykjanes Peninsula. It encompasses multiple geothermal reservoirs and aims to simulate the hot deeper roots of these systems. A regional conceptual model is created in LeapFrog based on divergent plate boundary theory and the regional volcanology to develop a lithological profile. This conceptual model was then directly used to setup a new TOUGH supercritical numerical model to a maximum depth of 7km. The model was calibrated by adjusting a 450 degreeCelsius iso-surface within the sheeted-dyke complex in the base of the system to generate the geothermal plumes. These plumes were then successfully temperature and pressure matched to the measured conditions in the known geothermal systems of Reykjanes, Svartsengi and Eldvörp. This study has successfully developed a large scale conceptual and supercritical numerical model encompassing multiple geothermal systems at great depths utilising a guiding workflow. It creates a strong platform for further investigation into areas such as the interaction between neighbouring geothermal systems or the long term regional ...